Identification of Differentially Expressed Genes from Ovarian Cancer Cells by MICROMAX™ cDNA Microarray System - Kwong-Kwok Wong; Rita S. Cheng; Samuel C. Mok (BioTechniques)
Using the MICROMAX™ cDNA microarray system, we were able to identify genes that are differentially overexpressed in ovarian cancer. A total of 30 putative genes, which are differentially overexpressed in ovarian cancer cell lines, were identified. The differential expression of some of these genes was further confirmed by real-time RT-PCR. Using this strategy, we have identified genes that either overexpress in all cancer cell lines or in only some cancer cell lines. Further characterization of these genes will allow them to be exploited in diagnosis, prognosis, anticancer therapy, and molecular classification of ovarian cancer.